2004
DOI: 10.1016/s0092-8674(04)00403-9
|View full text |Cite
|
Sign up to set email alerts
|

The β-Thymosin/WH2 Domain

Abstract: The widespread beta-thymosin/WH2 actin binding domain has versatile regulatory properties in actin dynamics and motility. beta-thymosins (isolated WH2 domain) maintain monomeric actin in a "sequestered" nonpolymerizable form. In contrast, when repeated in tandem or inserted in modular proteins, the beta-thymosin/WH2 domain promotes actin assembly at filament barbed ends, like profilin. The structural basis for these opposite functions is addressed using ciboulot, a three beta-thymosin repeat protein. Only the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
123
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 199 publications
(131 citation statements)
references
References 62 publications
8
123
0
Order By: Relevance
“…2A). The equivalent residues in ciboulot (Val-14 and Lys-31) and thymosin (Met-6 and Lys-18) sit directly in the binding interface in their respective structural models (16,31,32). In addition, our NMR data are supported by recently solved atomic structures of actin-bound WH2 domains from WASP and Scar (33).…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…2A). The equivalent residues in ciboulot (Val-14 and Lys-31) and thymosin (Met-6 and Lys-18) sit directly in the binding interface in their respective structural models (16,31,32). In addition, our NMR data are supported by recently solved atomic structures of actin-bound WH2 domains from WASP and Scar (33).…”
Section: Discussionsupporting
confidence: 71%
“…By NMR spectroscopy we found that the WH2-actin complex is similar to the previously described ciboulot D1-actin complex (16). This result supports the proposal that the two domains are evolutionarily related (17).…”
supporting
confidence: 89%
“…The increased rate of exchange of the yeast versus muscle peptide again is consistent with greater solvent exposure and perhaps greater propensity of the yeast monomer to open and twist. This area is also involved in the interaction of actin with binding proteins, such as cofilin (32), and WH2 domain proteins, such as formin (33), which are involved in controlling actin filament polymerization and turnover. Different flexibility and accessibility of this region to the solvent could be important for actin isoform specificity in the interaction of actin with its binding partners.…”
Section: Discussionmentioning
confidence: 99%
“…The actin-bound structures of the N-terminal half of ciboulot domain 1 (9) and that of a hybrid protein consisting of gelsolin domain 1 and the C-terminal half of T␤4 (10) have been reported. These structures have been combined into a model of T␤4-actin (10), and, although both T␤4 and ciboulot belong in the T␤ family, their structures have been described as representatives of WH2 (9,10).…”
mentioning
confidence: 99%